Effects of the Sedimentary Environment on Organic-Rich Shale in the Intracratonic Sag of the Sichuan Basin, China - Xuewen Shi; Jia Liu; Yiqing Zhu; Liang Xu; Yuran Yang; Chao Luo; Yanyou Li; Kesu Zhong; Xue Yang; Qiuzi Wu; Liang He; Demin Shi; et al. (Applied Sciences)
The enrichment of organic matter in high-quality marine shale is generally controlled by factors such as the redox conditions of sedimentary environments, productivity levels, terrigenous input, and ancient productivity. However, the controlling effect of the sedimentary environment on organic matter enrichment in intracratonic sag is still unclear. This study takes samples from the Qiongzhusi formation shale in southern Sichuan Basin as the research object, focusing on trace elements as well as rare earth elements in different stratigraphic intervals. The provenance of the Qiongzhusi formation shale is mainly terrigenous, with sediment sources mainly consisting of sedimentary rocks and granites. The primary sedimentary environment transitions from a continental margin setting, influenced by rift-related tectonic activity and sediment influx from adjacent landmasses, to an open oceanic environment characterized by mid-ocean ridge processes and oceanic plate subduction zones. During sedimentation, saline water was present, with predominant sedimentary environments ranging from shallow water to deep water continental shelves. The shale in the study area is characterized by a higher content of silicates and a lower content of carbonate minerals. Its siliceous sources are mainly influenced by biogenic and terrigenous debris, indicating higher ancient primary productivity and representing a favorable target for shale gas exploration.